OCCURRENCE OF INJURIES IN RHYTHMIC GYMNASTS ATHLETES (Fiep Bulletin - online, 2014)
In the Rhythm Gymnastic (RG), to reach the technical perfection and reproduce all the movements and exercises in their routines, the athletes must train and repeat these elements hundreds of times, and this can put the gymnasts in risk of injuries for excessively use in different structures and muscular groups. The aim of this study was to analyze the occurrence of injuries in practitioners of Rhythmic Gymnastic, the practice time and the volume of training in these athletes. The subjects were 266 female gymnasts, age ranging from 5 to 9 years old. They were participating on the VII National Tournament of Rhythmic Gymnastics, which has taken place from 16 to 19 November, 2006 in Florianópolis/Brazil. They were divided into four groups according to the age and the category they belonged to. Information was collected through the application of a direct questionnaire. Descriptive statistic was used for data analyzes. The mean age was 12,05 + 2,3 years. The athletes have been practicing the RG for about four years (53,2+28,5 months), with a training volume of approximately 18 weekly hours (1122,2+422min/weed). The occurrence of injuries was: adult (80%); juvenile (70,7%); infant (44%) e pre-infant (28 %). For all the categories the largest incidence of injuries occurred in the lower limbs: adult (knee - 36%); juvenile (foot - 25%); infant (foot - 14%) e pre-infant (groin - 8%). The spine was significantly smitten, especially within the adult (32%) and juvenile (18%) category. We confirmed the tendency of relevant injuries in the lower limbs due to the extreme movements executed with them during the RG practice. Through this study, we confirm the importance of preventive programs aiming the minimization of injuries in this sport.
Keywords: Rhythmic Gymnast; Injuries; Training Volume